(untitled) (Research, Society and Development, 2020)
Synthetic hormonal plant growth promoter (HPGP) has been used in agriculture, especially kinetin (KIN, cytokinin), gibberellic acid (GA3, gibberellin), and indolbutyric acid (IBA, auxin). The objective of this work was to evaluate rates and methods of application of a HPGP product (0.09 g L-1 of KIN; 0.05 g L-1 of GA3; 0.05 g L-1 of IBA) and its effects on wheat seedling growth. Two independent experiments were carried out in a greenhouse. The first was performed on Germitest® paper and the second in soil. In both cases, it was used a completely randomized design. The first trial, with 10 replicates, was carried out in a 2 × 2 × 4 factorial arrangement, being two wheat genotypes, two HPGP rates applied on the seeds, and four periods of seedling growth, totaling 160 experimental units. The second trial had four replicates, with treatments disposed in a 2 × 2 × 2 factorial arrangement, being two wheat genotypes, two HPGP rates applied on the seeds, and two HPGP rates applied on the leaves, totaling 32 experimental units. It was evaluated the growth of roots (number of roots/seedling and total root length/seedling) and the growth of leaves (length, width, and area). The application of HPGP on the seeds delayed the initial root growth and the leaf area expansion. However, this inhibitory effect was reversed along with the advance of seedling age. The combined application of HPGP on the seeds and on the leaves caused an antagonistic effect, with systematic growth reduction of wheat seedling roots.